A PROSPECTIVE STUDY TO ASSESS THE QUALITY OF LIFE AMONG THE PATIENTS OF GENERALIZED TONIC-CLONIC SEIZURE RECEIVING TREATMENT PHENYTOIN PLUS CLOBAZAM VERSUS SODIUM VALPROATE PLUS CLOBAZAM THERAPY - Sharma, Ranjana; Kothari, Saroj; Pathak, Akshat; Dixit, Prashant (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The objective of the study was to compare effect of phenytoin plus clobazam (Group 1) and sodium valproate plus clobazam therapy (Group 2) on quality of life among generalized tonic-clonic seizures (GTCS) patients attending neurology out-patient department at the tertiary care center in Gwalior district. Methods: The present study was a prospective study conducted between period of February 2019 and January 2020 on 45–45 patients each receiving either phenytoin plus clobazam or sodium valproate plus clobazam dual therapy for the treatment of patients with GTCS. Frequency, percentage, mean, standard deviation, independent student t-test, Chi-square test, and one-way repeated measures of ANOVA were applied, and Bonferroni adjustment was calculated using SPSS version 20 software. P<0.05 was considered to be statistically significant. Results: For question 1, in Group 1, mean score was 3.29±0.45 at 0 month (baseline), which reduced to 2.51±0.50 and 2.11±0.48 at 3 and 6 months, respectively. In Group 2, mean score was 3.31±0.46 at 0 month, which reduced to 2.35±0.48 and 1.95±0.29 at 3 and 6 months. For question 2, in Group 1, mean score was 3.44±0.54 at 0 month (baseline), which reduced to 2.55±0.54 and 2.22±0.51 at 3 and 6 months, respectively. In Group 2, mean score was 3.64±0.48 at 0 month, which reduced to 2.77±0.55 and 2.44±0.54 at 3 and 6 months, respectively. There was statistically significant improvement seen within the group at 3 and 6 months as compared to baseline in both groups for question 1, question 2, question 3, question 4; p<0.01. Conclusion: It can be concluded that both combinations of our study groups have a better impact on quality of life from baseline till the end of the study. However, on comparison between them, we have not found a statistically significant difference.